Social-scientific criticism in Nigerian New Testament scholarship - Uwaegbute, Kingsley I. (HTS teologiese studies, 2021)
The use of the social sciences in the interpretation of the New Testament emerged from the 1970s and has become a standard methodology for interpreting the New Testament. However, it has not been significantly used in the interpretation of the New Testament in Nigeria by biblical scholars. This article discusses what social-scientific criticism is and the need for its application in the interpretation of the New Testament by Nigerian New Testament scholars for a better understanding of the New Testament and the people, beliefs and teachings it presents and contextualisation in the face of changing contexts of Christianity in Nigeria.Contribution: As far as we know, this article is the first one written on using social-scientific criticism to interpret the New Testament in the Nigerian context. It therefore contributes to the need for a multidisciplinary approach to interpreting the New Testament in Nigeria in particular and Africa in general. It therefore contributes also on methodological considerations with regard to interpreting the New Testament.